REGIONAL IDENTITY: THEORETICAL AND METHODOLOGICAL ASPECT OF RESEARCH - S. Konovalov (Вестник Северо-Кавказского федерального университета)
The article presents the author's interpretation of the concept of «regional identity» as a system characteristic of a territory, reflecting the perception and evaluation of its entities. It is substantiated that «regional identity» includes an external component and an internal one, having a subjective and objective character, determined by the source of information provided. The principle of assessing regional identity is defined. In conditions when the characteristics of the external and internal components of the regional identity coincide and have high objective evaluations, then one should speak of a positive regional identity. In all other cases, one should speak of a negative regionally identity and the presence of an «identification gap».